Blocking variant surface glycoprotein synthesis alters endoplasmic reticulum exit sites/Golgi homeostasis in Trypanosoma brucei. (6th April 2018) - Ooi, Cher‐Pheng; Smith, Terry K.; Gluenz, Eva; Wand, Nadina Vasileva; Vaughan, Sue; Rudenko, Gloria
Abstract : The predominant secretory cargo of bloodstream form Trypanosoma brucei is variant surface glycoprotein (VSG), comprising ~10% total protein and forming a dense protective layer. Blocking VSG translation using Morpholino oligonucleotides triggered a precise pre‐cytokinesis arrest. We investigated the effect of blocking VSG synthesis on the secretory pathway. The number of Golgi decreased, particularly in post‐mitotic cells, from 3.5 ± 0.6 to 2.0 ± 0.04 per cell. Similarly, the number of endoplasmic reticulum exit sites (ERES) in post‐mitotic cells dropped from 3.9 ± 0.6 to 2.7 ± 0.1 eight hours after blocking VSG synthesis. The secretory pathway was still functional in these stalled cells, as monitored using Cathepsin L. Rates of phospholipid and glycosylphosphatidylinositol‐anchor biosynthesis remained relatively unaffected, except for the level of sphingomyelin which increased. However, both endoplasmic reticulum and Golgi morphology became distorted, with the Golgi cisternae becoming significantly dilated, particularly at the trans‐face. Membrane accumulation in these structures is possibly caused by reduced budding of nascent vesicles due to the drastic reduction in the total amount of secretory cargo, that is, VSG. These data argue that the total flux of secretory cargo impacts upon the biogenesis and maintenance of secretory structures and organelles in T. brucei, including the ERES and Golgi. Abstract : Variant surface glycoprotein (VSG) is the most abundant protein (~10% total) of bloodstream form Trypanosoma brucei, comprising the bulk of the secretory cargo. We show that blocking VSG synthesis resulted in a reduction in the number of secretory structures, including endoplasmic reticulum exit sites and Golgi. Both endoplasmic reticulum and Golgi morphology became distorted, with significant dilation of the trans Golgi cisternae. Total secretory flux, therefore, appears to affect the homeostasis of these secretory structures in T. brucei .